Evaluation of symptomatic maxillary sinus pathologies using panoramic radiography and cone beam computed tomography-influence of professional training - Michael Dau; Paul Marciak; Bial Al-Nawas; Henning Staedt; Abdulmonem Alshiri; Bernhard Frerich; Peer Wolfgang Kämmerer (SpringerOpen, 2017)
Abstract Background A comparison of panoramic radiography (PAN) alone and PAN together with small field of view cone beam computed tomography (sFOV-CBCT) for diagnosis of symptomatic pathologies of the maxillary sinus was carried out by clinicians of different experience. Methods Corresponding radiographic images (PAN/sFOV-CBCT) of 28 patients with symptomatic maxillary sinus pathologies were chosen and analyzed by two general practitioners (GP), two junior maxillofacial surgeons (MS1), and three senior maxillofacial surgeons (MS2) via questionnaire. Results Visibility of maxillary pathologies in PAN was significantly different between the groups (GP 39%, MS1 48%, MS2 61%; p < 0.05). The number of incidental findings varied within examiner groups in PAN with a significant increase in MS2 (p = 0.027). The majority of examiners rated an additional sFOV-CBCT as "reasonable"/"required" with a significant influence of the examining groups (GP 98.2%, MS1 94.6%, MS2 80.9%; p = 0.008). In 58% of cases, an additional sFOV-CBCT was seen as "affecting therapy" with significant differences between the groups (GP 68%, MS1 50%, MS2 55%; p < 0.001). Conclusions PAN alone is not sufficient for the evaluation of pathologies of the maxillary sinus. But, depending on the examiners' clinical experience, it remains a useful diagnostic tool. Along with the observers' training, significant benefits of an additional sFOV-CBCT for evaluation of symptomatic maxillary sinus pathologies were detected.